Rancang Bangun Smart Air Purifier - Rizadi Sasmita Darwis; Widi Kurniawan (Politeknik Caltex Riau, 2021)
The quality of the inhaled air affects the immune system and human health. If the air that is inhaled is dirty, it can interfere with daily human activities and one way to prevent it is to need a device that can identify and clean dirty air so that the need for clean air can be met and daily human activities will run smoothly. So in this final project, the author designed a Smart Air Purifier device to overcome the air contaminated by PM2.5 and PM10. The average error percentage value of the PM10 GP2Y1010AU0F sensor reading is 12.80%. This Smart Airpurifier device can perform purification in all types of rooms and different types of rooms. The advantage of this device is that it can clean air with various pollutants such as cigarette smoke, to PM10 particles below 10 g/m3. The effectiveness of the mode on the device has advantages and disadvantages to sterilize the air in the room. For example, when the PM10 value is above 300 g/m3, the high mode is effective for sterilizing dirty air, especially smokeKeywords: NodeMCU ESP8266, GP2Y1010AU0F Dust Sensor, Android, Realtime